Assessing aesthetic relevance: Children's book selection in a digital library - Kara Reuter (Journal of the American Society for Information Science and Technology, 2007)
Recreational reading among young people is reportedly on the decline in the United States. Some researchers have suggested that supporting children’s strategies for book selection is crucial to encouraging children to engage with books, indicating that improving these strategies might increase the amount of reading they do. In response, this study explores how elementary-school children select books for recreational reading using a digital library. The work extends traditional models of relevance assessment with reader-response theory, employing the concept of “aesthetic relevance”: the potential of a document to provide a suitable reading experience. Individuals define aesthetic relevance in personal terms and apply it as they assess documents, much as they do in traditional relevance assessment. This study identified a total of 46 factors organized along seven dimensions that influence children’s assessment of the aesthetic relevance of books during selection. The analysis yielded differences in the prevalence of the aestheticrelevance factors that children mention at various stages of book selection. In addition, the children exhibited differences by age and subtle differences by gender in the frequency of mention of various aesthetic-relevance factors. Recommendations drawn from the findings are offered to improve systems design and literacy education in order to enhance children’s access to books and to promote recreational reading.
Keywords: évaluation; genre; jeunesse; lecture numérique; recreational reading